HUBUNGAN KESIAPAN BELAJAR DALAM KURIKULUM MERDEKA TERHADAP HASIL BELAJAR DALAM PELAJARAN MATEMATIKA PADA MATERI PERKALIAN KELAS V SD NEGERI 10 BANDA ACEH - Muthmainnah, Annisa; Isa, Muhammad; Suryawati, Indah (Jurnal Seramoe Education, 2025)
Learning readiness is the initial stage of preparation before starting the learning process. The formulation of the problem in this study is whether there is a relationship between learning readiness in the independent curriculum and learning outcomes in mathematics lessons in grade V multiplication material of SD Negeri 10 Banda Aceh. This study aims to determine the relationship between learning readiness in the independent curriculum and learning outcomes in mathematics lessons in grade V multiplication material of SD Negeri 10 Banda Aceh. The population in this study is grade V students of SD Negeri 10 Banda Aceh. Sampling was carried out by random sampling technique, which was selected by the VA class as many as 18 students. Data collection techniques are in the form of giving questionnaires and tests to students, namely pre-test and post-test. The data was processed using SPSS 26 with a significant level of 5% with the test - Paired samples obtained a mean value for the pre-test score of 40.55 and a post-test value of 42.77. The results of the t-test using the paired sample test showed that the t-value of the calculated t-0.720 and the t-calculated table of the sig (2-tailed) was 0.481 (t calculated < t-table). Thus, the final conclusion obtained is that there is a significant correlation between learning readiness in the independent curriculum and learning outcomes in mathematics lessons in grade V multiplication material of SD Negeri 10 Banda Aceh.